Consequences of covid-19 on the international trade in goods and services: Forecasts, developments, restrictions - Camelia Milea (Financial Studies, 2020)
The Covid-19 pandemic has created an unprecedented situation, driven by the measures taken by national governments to fight the spread of the disease, through which companies have been temporarily shut down, the movement of people and goods has been restricted, and supply chains have been disrupted. Although in the first part of 2020, there has been a reduction in international trade flows due to the decline in economic activity, there has been an increase in imports and exports of agricultural products, food and beverages for final consumption and medical products. The analysis shows that global trade in services has declined less than trade in goods. An additional factor of stress on international trade has been the export bans and restrictions. Declining production in China, the world's largest supplier of intermediate goods, is likely to affect the economies in many countries.
Keywords: F01; F14; F17; 330; Exports; Imports; Prognoses; Non-tariff Barriers; Changes; Effects